Entre a "malhada e o parque" : uma análise sobre o Povoado Bom Jardim e o Parque Nacional Serra de Itabaiana-SE - Souza, Claydivan Wesley dos Santos (2014)
Face of overwhelming environmental crisis in contemporary society, it is necessary to understand the changes occurring in the way of producing conceptions of the environment as well, in the way of using natural resources. The aim of this study was to analyze the socio-environmental changes in the Bom Jardim community after the institutionalization of Parque Nacional Serra de Itabaiana. The study area was Bom Jardim community, located in Itabaiana, distant about 9 km from the town and the Parque Nacional Serra de Itabaiana - PARNASI, institutionalized in 2005 and entered the cities of Areia Branca, Itabaiana, Itaporanga D Ajuda, Laranjeiras and Campo do Brito. Using the qualitative method with the anchoring of ethnography analyzing the main representations of the Bom Jardim community on Sierra Itabaiana, considering that environmental conservation is not the only ecological, but especially social problem as well, we investigated the everyday of farmers in Bom Jardim, by understanding the work in the spotted. Thus, it was concluded that while there are no fences, regular inspections, and actual rapprochement between management PARNASI with the community, are the tents that ensure family survival in Bom Jardim, though, the social actors who are between malhada and park not be viewed in the context of environmental public policies.